Evidences in resemblance of archaeological structures of Kesariya and Borobudur Stupa. Issue 1 (May 2021) - Sinha, I; Tucunan, K P
Abstract: India's cultural interface with southeast Asia started around the beginning of Christian era with the discovery of monsoon which traverses a fixed path or direction with remarkably predictable timing or annual cycle thereby generating confidence of safe and convenient maritime trade from the west as well as east Indian coast. This article is aimed to seek the connections and relation between India and Indonesia through deep observations and comparison to the Kesariya (India) and Borobudur (Indonesia). Using Ethnology approaches some evidences has been found